(untitled) (Balthazar, 2020)
This paper critically examines the main theories concerning immaterial capitals’ nature, aiming to show how material capital’s logic could be used to interpret a wide range of non-material fields. A specific definition of capital is used to overcome the distinction between material and immaterial. This is accomplished on the one hand by recovering Marx’s classical analysis, on the other hand by introducing corrective elements taken from Robinson and Federici. Thus, the definition is used to construct a materialistic interpretation of immaterial capitals, with particular attention to their relational nature as social, historical and situated relationships, to the issues of primitive accumulation as a violent process and as a dialectic of expropriation and destruction, to the production of scarcity and phenomena of monopolisation, and, finally, to the functions of exploitation and social domination of the capital. The theoretical results thus obtained are then applied to the case study of the invention of white race in the South of United States. For this purpose, Allen’s historical reconstruction and Bethencourt’s research about racisms are employed, with some reflections on the role and approprative function of discourses, representations and theories in the process of constitution of whiteness as an immaterial capital.